Cubital Tunnel Syndrome: Review of Diagnosis and Management - Ferguson, Devin Patrick; Grewal, Ruby (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Cubital tunnel syndrome is one of the most common upper extremity nerve entrapment conditions. Clinical examination and electrodiagnostic studies assist in the diagnosis. Mild cases can be successfully treated conservatively, aiming to reduce traction and compression on the nerve. Surgical management of cubital tunnel syndrome is increasing in frequency. Multiple surgical options exist ranging from simple decompression to decompression and anterior transposition of the nerve. There is no preferred surgical technique. It is critical to reduce the risk of recurrent cubital tunnel syndrome. Revision surgical procedures have worse outcomes than primary surgical procedures.
Keywords: Cubital tunnel syndrome; diagnosis; management